'New Wave' Student Voice and the Renewal of Civic Society. (1st November 2004) - Fielding, Michael
Abstract : The re-emerging field of 'student voice' has the potential to offer an important contribution to education for civic society. An exploration of what 'student voice' aspires to and what it actually does suggests quite different sets of possibilities for educational and civic renewal. A new intellectual framework is offered in the hope that it might contribute further to democratic aspirations and emergent realities.